Dublin English : evolution and change - Hickey, Raymond, 1954- (Varieties of English around the world. General series ;, 2005)
"The present book describes the English language in all its facets as spoken in present-day Dublin, the capital of the Republic of Ireland. It covers the entire range of its history since the first arrival of English there several hundred years ago. Apart from the evolution of English in the capital, the book also concentrates on the significant changes which have been taking place in the speech of Dublin in the past 15 years or so."--Jacket.